An investigation of cadmium(II) and nickel(II) adsorption by chitin graft covolymer - Jose, A. R.; Bach, E. E.; Vargas, R. R.; Soares, A. W.; De Queiroz, AAA (Wiley-Blackwell, 2004)
Chitin hydrogels of poly(vinylpyrrolidone) (VP) were prepared by means of the hydrogen peroxide graft copolymerization process. The effect of the VP grafted chain on water diffusion through the biopolymer was studied. Fourier transform infrared spectra of the VP-g-Ch showed an increase in the intensities of the hydroxyl and carbonyl stretching bands indicating a reduction in the hydrogen bonding of chitin. An investigation was undertaken regarding the adsorption of nickel(II) and cadmium(II) ions from aqueous solutions by the VP grafted chitin and the effects of the grafting degree on the Cd2+ and Ni2+ sorption were studied. The Cd2+ and Ni2+ adsorption equilibrium data correlate well with the Freundlich equation. The results indicate that the Ch-g-VP graft copolymer under investigation is a potentially powerful chelating material that can be employed for Ni2+ and Cd2+ ion removal from wastewater effluents. (C) 2004 Wiley Periodicals, Inc.
Keywords: graft copolymers; hydrogels; chitin; metal-polymer complexes; cadmium(II) and nickel (II) sorption